Managing Multicultural Islamic Education through Conflict Resolution Learning Development in Indonesia - Thoyib, Muhammad; Subandi, Subandi; Harsoyo, Roni (Universitas Islam Negeri Raden Intan Lampung, 2021)
Along with the frequent social conflicts in Indonesia, the multicultural reality of this country is becoming increasingly urgent to be reconstructed so that it can become an